The Effect of Monosodium Glutamate on the Lee Index in Mice (Mus Musculus) - Innayah, Nurul; Azam, Mahalul; Yuniastuti, Ari (Universitas Negeri Semarang, 2021)
Obesity is the buildup of abnormal or excessive fat that can be detrimental to health. High flavor-flavoring consumption or monosodium glutamate (MSG) is one of the factors contributing to the increase in obesity of the Indonesian population. This study aims to analyze the effect of MSG on giving to Lee's index in mice. The Lee index is one of the indicators in determining mice obesity. The type of research was pure laboratory experimental research, with the design Post Test Only Control Group. The mice were divided into four random clusters. Each cluster contained six mice. The control cluster was given standard feed + drink, cluster I was given standard feed + drink + MSG 10.4 mg / 20gbb, cluster II was given standard feed + drink + MSG 20.8 mg / 20gbb and cluster III was given standard feed + drink + MSG 26 mg / 20gbb for 28 days. Day 29 was the weight lift and the length to calculate the lee index. Data normality analyze used Spahiro Wilk and the homogeneity test used Levene's test. The results of the variance homogeneity test showed that the value of p = 0.374, so that the lee index value of each cluster did not have a significant difference (p> 0.05). Then continued with the One Way Anova test, the value of p = 0.246 (meaningful if p <0.05). It could be concluded that the provision of MSG 4 grams, 8 grams, and 10 grams did not have a significant effect on the lee index value in mice between the control cluster and the treatment cluster.